Determinan Penghambat dan Strategi Kejaksaan Negeri Boalemo dalam Melindungi Anak sebagai Korban Pencabulan - Pelu, Febriyanti; Wantu, Fence M; Mamu, Karlin Z (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze the determining factors and strategies implemented by the Boalemo District Attorney's Office in protecting children as victims of sexual abuse. The main issue raised is how internal and external obstacles affect the effectiveness of legal protection, as well as what strategies have been and can be implemented to optimize protection for victims. The research method used is an empirical legal approach with data collection techniques through literature review, in-depth interviews with public prosecutors at the Boalemo District Prosecutor's Office, and documentation of child sexual abuse cases handled over the past five years. The data was analyzed using qualitative descriptive methods to obtain a comprehensive picture of the obstacles and legal protection efforts. The results of the study indicate that the main obstacles to legal protection for child victims of sexual abuse in Boalemo include limited trained human resources, a lack of child-friendly facilities and infrastructure, weak coordination between institutions, psychological pressure on victims, and challenges in proving cases in court. Strategies implemented include professional prosecution, legal and psychological assistance, restitution, special training for prosecutors, development of child-friendly facilities, and application of restorative justice principles. The impact of this study shows that these efforts have made a positive contribution to the legal protection of children, although strengthening is still needed in various aspects, especially in cross-sectoral synergy and institutional capacity building. These findings are expected to serve as a reference for the development of child protection policies and practices at the regional and national levels.